Induction and evaluation of benomyl-tolerant mutants of Trichoderma viridefor biological control of Botrytis grey mould of chickpea - and K. RAGHU1, P.K. MUKHERJEE1, M.P. HAWARE2 (Indian Phytopathology, 2002)
Benomyl-tolerance is absent in the natural population of Trichoderma spp. used in the biocontrol of plant pathogenic fungi. Stable benomyl-tolerant mutants of Trichoderma viride isolate T-15 were obtained for the integrated biocontrol of Botrytis grey mould of chickpea caused by B. cinerea. Some of the mutants are hyper-producers of antifungal substances in culture filtrates, and are equally effective as the wild type strain in their disease control potential. The usefulness of these mutants in a biocontrol programme is discussed.